Case Report: Generalized lipodystrophy following immune-checkpoint inhibitor therapy - Lee, Andrew-Hyun; Hui, Rina; Gunton, Jenny E. (Frontiers in Endocrinology, 2025)
Immune-related adverse events secondary to immune checkpoint inhibitors (ICI) are increasingly recognised. Lipodystrophy is a rare condition which results in the selective loss of adipose tissue. We describe a case of a 48-year-old woman who had been treated with pembrolizumab for lymph node-positive breast cancer. She was referred to the diabetes service for worsening hyperglycemia, hypertriglyceridemia, and rapid onset of weight loss which occurred a year into pembrolizumab therapy. Examination was consistent with a diagnosis of severe lipodystrophy with severe loss of facial and limb adipose tissue. Investigations including a low leptin level and loss of adiposity on whole body composition analysis were consistent with this diagnosis. A trial of pioglitazone was associated with an improvement in insulin resistance and hypertriglyceridemia, although no improvement in her facial lipodystrophy was observed.